The Role of the Enterohepatic Circulation of Bile Salts and Nuclear Hormone Receptors in the Regulation of Cholesterol Homeostasis: Bile Salts as Ligands for Nuclear Hormone Receptors - Richard N Redinger (Canadian Journal of Gastroenterology)
The coordinated effect of lipid activated nuclear hormone receptors; liver X receptor (LXR), bound by oxysterol ligands and farnesoid X receptor (FXR), bound by bile acid ligands, act as genetic transcription factors to cause feed-forward cholesterol catabolism to bile acids and feedback repression of bile acid synthesis, respectively. It is the coordinated action of LXR and FXR, each dimerized to retinoid X receptor, that signal nuclear DNA response elements to encode proteins that prevent excessive cholesterol accumulation and bile salt toxicity, respectively. LXR helps prevent hypercholesterolemia by enhancing transporters for cholesterol efflux that enhance reverse cholesterol transport, while FXR enhances intestinal reabsorption and preservation of bile salts by increasing the ileal bile acid binding protein. FXR also targets sodium taurocholate cotransport peptide and bile salt export pump (protein) genes to limit bile salt uptake and enhance export, respectively, which prevents bile salt toxicity. Other nuclear hormone receptors such as pregnan X receptor, which share the obligate partner, retinoid X receptor, and vitamin D receptor also function as bile acid sensors to signal detoxification by hydroxylation of toxic bile acids. Pharmacologically targeted receptor agonists (or antagonists) may be developed that alter cholesterol and bile salt concentrations by modulating nuclear hormone receptors and/or their coactivators or corepressors to positively affect cholesterol homeostasis and bile salt metabolism. It is the coordinated transcription factor action of LXR, which responds to ligand binding of circulating oxysterols in both liver and peripheral tissues, and FXR responding to bile salts within the enterohepatic circulation that make possible the regulation of cholesterol and bile acid homeostasis.